Diagnostic Accuracy Of Mr Spectroscopy For The Detection Of Supratentorial Neoplastic Space-Occupying Lesions Of The Brain By Taking Histopathology As The Gold Standard At Tertiary Care Hospital, Karachi - Mehak, Mehak; Farhan, Naureen; Shams, Amber; Sagar, Bhavesh; Zafar, Faryal (Journal of Neonatal Surgery, 2025)
Objective: To determine the diagnostic accuracy of MR spectroscopy for the detection of supratentorial neoplastic space-occupying lesions of the brain by taking histopathology as the gold standard at Tertiary Care Hospital, in Karachi. Design: Cross-sectional study Place and Duration of Study: This study was conducted from 11th May 2024 to 10th Nov 2024 at the Department of Radiology, Ziauddin Hospital Methodology: The diagnosis of benign and malignant intracranial lesions based solely on imaging methods remains a challenging problem. Patients aged 20 to 70 years underwent MR spectroscopy for the detection of supratentorial neoplastic space-occupying lesions of the brain. A histopathological assessment of biopsy specimens was performed to establish the final diagnosis. Diagnostic performance measures, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy of MR spectroscopy, were calculated using histopathology as the gold standard. Results: The average age of the patients was 40.68±12.05 years (Range: 21-69). There were more males (61.24%) than females (38.76%). The prevalence of neoplastic space-occupying lesions was 75.97% [95% CI: 68.6%–83.3%]. The sensitivity, specificity, PPV, NPV, and diagnostic accuracy of MR spectroscopy for detecting supratentorial neoplastic space-occupying lesions of the brain were 80.61% [95% CI: 71.69–87.22], 87.10% [95% CI: 71.15–94.87], 95.18% [95% CI: 88.25–98.11], 58.70% [95% CI: 44.34–71.71], and 82.17% [95% CI: 74.67–87.82], respectively Conclusion: Magnetic Resonance Spectroscopy (MRS) offers a reliable non-invasive method for distinguishing brain lesions, reducing the need for biopsies and improving patient outcomes..